2021
DOI: 10.1177/1362361320981314
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and screen time among youth with autism: A longitudinal analysis from 9 to 18 years

Abstract: To date, studies using cross-sectional methodologies make up a majority of the literature surrounding children with autism spectrum disorders and participation in physical activity and screen time. Longitudinal studies are needed to examine how physical activity and screen time behaviors co-develop for children with and without an autism spectrum disorder. To address this research gap, this study compared how physical activity and screen time levels changed over time (9 to 18 years of age) between youth with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
(65 reference statements)
0
25
0
Order By: Relevance
“…In addition, a multitude of studies have identified that by adolescence, youth with ASD tend not to engage in regular physical activity, particularly when compared to peers without disabilities [10-12, 16, 39]. A plethora of factors have been identified that may contribute to low physical activity engagement among adolescents with ASD, including time and financial constraints, a lack of opportunities, and social barriers associated with the stress that arises from engaging in and initiating social interactions during activities [16,40]. Taken together, the current study along with prior research [10-12, 22, 37, 39] make it clear that adherence to physical activity guidelines is problematic for youth with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a multitude of studies have identified that by adolescence, youth with ASD tend not to engage in regular physical activity, particularly when compared to peers without disabilities [10-12, 16, 39]. A plethora of factors have been identified that may contribute to low physical activity engagement among adolescents with ASD, including time and financial constraints, a lack of opportunities, and social barriers associated with the stress that arises from engaging in and initiating social interactions during activities [16,40]. Taken together, the current study along with prior research [10-12, 22, 37, 39] make it clear that adherence to physical activity guidelines is problematic for youth with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…While research examining the prevalence and benefits of meeting multiple 24-h movement guidelines among youth is emerging [4,5], the extension of this integrated framework to study the health behaviors among youth with disabilities, such as those with autism spectrum disorder (ASD), is limited. To date, studies have demonstrated that youth with ASD tend to engage in inadequate amounts of physical activity [10][11][12][13] and sleep [14,15], and an overabundance of recreational screen time [16,17], which may lead to undesirable physical and psychological outcomes, such as overweight or obesity [11,18,19], health concerns [19,20], and poor quality of life [20,21]. However, these studies have largely explored movement behaviors in isolation, and few have explored the prevalence of meeting multiple 24-h movement guidelines among youth with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, motor services such as occupational and physical therapy (OT and PT) are known to reduce with increasing age along with increase in sedentary/physical inactivity time; which seems counterintuitive if motor difficulties in children with ASD are not reducing with age (Bremer & Cairney, 2020;Dahlgren et al, 2021;Monz, Houghton, Law, & Loss, 2019;Srinivasan et al, 2014Srinivasan et al, , 2021. For example, youth with ASD showed a decrease in light and moderate to vigorous physical activity levels between 9 and 18 years compared to age-matched, typically developing children; along with more time spent engaging with video games (Dahlgren et al, 2021). Overall, there seems to be a stable pattern of motor difficulties across childhood and into adolescence which may further negatively impact children with ASD's physical activity levels and subsequently their physical/mental health and well-being (for other factors influencing physical activity levels in ASD refer to Jachyra et al, 2021).…”
Section: Age-related Motor Differences In Asdmentioning
confidence: 99%
“…A recent SPARK study analysis replicated this finding with 87% of the sample presenting with a risk for general motor difficulties in children with ASD that did not change between 5 and 15 years (Bhat, 2020). Nevertheless, motor services such as occupational and physical therapy (OT and PT) are known to reduce with increasing age along with increase in sedentary/physical inactivity time; which seems counterintuitive if motor difficulties in children with ASD are not reducing with age (Bremer & Cairney, 2020; Dahlgren et al, 2021; Monz, Houghton, Law, & Loss, 2019; Srinivasan et al, 2014, 2021). For example, youth with ASD showed a decrease in light and moderate to vigorous physical activity levels between 9 and 18 years compared to age‐matched, typically developing children; along with more time spent engaging with video games (Dahlgren et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, compared to children without ASD, those with the diagnosis engage in significantly less physical activity [ 52 , 53 ], have less sleep [ 54 ] and have more recreational screen time [ 55 , 56 ].…”
Section: Physical Activity With a Special Emphasis On Asdmentioning
confidence: 99%